A systematic literature review and future research agenda on the reducing single use plastic in the context of consumer intention - Luh De Dwi Jayanthi; Herdis Herdiansyah; Nicholas Simarmata (Institute for Advanced Science Social, and Sustainable Future, 2026)
Background: The onslaught of plastic pollution is largely driven by consumer activities that have widespread environmental and ecological impacts. This study examines the scientific literature on consumer intention related to reducing single-use plastic, a pivotal factor of the United Nations’ Sustainable Development Goals (SDGs) for 2030, specifically the goal of responsible production and consumption. Methods: The data used in this analysis were identified through a search of the Scopus database using keywords such as reduce* and plastic* and behavior* and intention*, covering 49 publications in English over the last ten years (from 2015 to 2025). Five primary themes emerged using NVivo and VOSviewer for thematic analysis, highlighting the multifaceted nature of consumer intention. Findings: Bibliometric analysis identified four clusters: behavior change and plastic consumption, the actor of reducing and managing single-use plastic, policy intervention and decision-making, and human drivers and plastic pollution. Each cluster was expanded into a series of meaningful codes through NVivo-assisted thematic analysis. Conclusion: The success of any effort in reducing single-use plastic inevitably relies on how the problem is defined and perceived. In this sense, we also conclude several factors that contribute to reducing single-use plastic: the source of single-use plastic usage, single-use plastic behavior, the type of single-use plastic, production, and management. Novelty/Originality of this article: This comprehensive and cross-contextual study examines consumer intentions toward reducing single-use plastic use. Unlike previous reviews that focus on individual sectors, this study systematically integrates evidence from households, restaurants, cafés, and corporate settings. This approach enables the identification of overarching behavioral patterns, context-specific drivers, and underexplored research areas, contributing to a comprehensive theoretical and practical understanding of single-use plastic reduction. Furthermore, this study has outlined three promising future research directions that aim to enhance the quantity and quality of this study.